Reproducing Religious Legitimacy: Symbolic Power in The Haul Tradition - Nisa, Khalimatu (Proceedings of International Conference on Muslim Society and Thought, 2024)
Haul, which is celebrated in various regions in Indonesia, is aimed at commemorating the death of Islamic scholars or figures considered to have contributed significantly in the society. In Indonesia, several haul(s) are held on a large scale and involve hundreds of thousands to millions people. For example, the haul of Abah Guru Sekumpul in Martapura, South Kalimantan, and the haul of Habib Ali bin Muhammad Al-Habsyi in Solo, Central Java. In rural areas, haul(s) are held in a simpler mean to commemorate local Islamic scholars. Haul(s) are usually organized by the heirs, although over time, initiatives for haul(s) have also emerged from outside the family circle. Predominantly, the haul tradition is closely intertwined with pesantren tradition. Haul, as its literal definition, becomes an annual agenda as done by Pesantren Al-Munawwir Krapyak, Yogyakarta, in memorizing its late founder, KH. Muhammad Munawwir. This Quranic scholar not only established the pesantren but also founded a network of Quranic scholar epistemology in Nusantara. Passing away in 1942, his haul celebration becomes increasingly massive each year. As a tradition, haul is seen more in terms of ritual or da’wa aspects. This paper aims to scrutinize the political context behind the haul tradition. By utilizing Bourdieu's theory of symbolic power, this paper argues that haul is an effort to produce religious legitimacy over time. Through a case study method on the commemoration of KH. Muhammad Munawwir's haul, this research shed light on power relations through the analysis of arenas, modalities, and habitus behind the tradition.